Cultivar-Dependent Responses of Eggplant (Solanum melongena L.) to Simultaneous Verticillium dahliae Infection and Drought - Tani, Eleni; Kizis, Dimosthenis; Markellou, Emilia; Papadakis, Ioannis; Tsamadia, Dimitra; Leventis, Georgios; Makrogianni, Despoina; Karapanos, Ioannis (Frontiers in Plant Science, 2018)
Several studies regarding the imposition of stresses simultaneously in plants have shown that plant responses are different under individual and combined stress. Pathogen infection in combination with drought can act both additively and antagonistically, suggesting a tailored-made plant response to these stresses. The aforementioned combination of stresses can be considered as one of the most important factors affecting global crop production. In the present research we studied eggplant responses to simultaneous Verticillium dahliae infection and drought with respect to the application of the individual stresses alone and investigated the extent to which these responses were cultivar dependent. Two eggplant cultivars (Skoutari and EMI) with intermediate resistance to V. dahliae were subjected to combined stress for a three-week period. Significant differences in plant growth, several physiological and biochemical parameters (photosynthesis rate, leaf gas exchanges, MDA, Proline) and gene expression, were found between plants subjected to combined and individual stresses. Furthermore, plant growth and molecular (lipid peroxidation, hydrogen peroxide, gene expression levels) changes highlight a clear discrimination between the two cultivars in response to simultaneous V. dahliae infection and drought. Our results showed that combined stress affects significantly plants responses compared to the application of individual stresses alone and that these responses are cultivar dependent.